SPECIES RICHNESS AND HOST DIVERSITY OF SYRPHID FLIES (SYRPHIDAE : DIPTERA) OF JAMMU AND KASHMIR STATE ( INDIA) - BHAGAT, R.C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
The present communication incorporates an updated checklist of syrphid flies of Jammu and Kashmir region, including 41 species, belonging to 21 genera, with their host aphid/plant species and distributional range. The host plant- range of 11 species of aphidivorous syrphid species, has been elaborated, suppressing populations of 38 aphid species, damaging 36-host plant species. Data on host-plant diversity of 24 species of adult syrphids, attracted to the flowers of 47 plant species, under 30 genera, has also been provided.